Preparation method of high-strength cement-based water permeable brick

By using specific proportional materials and treatment technologies in the preparation of permeable bricks, the problem of insufficient strength and durability of existing permeable bricks is solved, and high strength, good permeability and durability are improved to adapt to the needs of harsh environments.

CN119219385APending Publication Date: 2024-12-31KAIHUA MINGHUI PLASTIC PRODUCTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411447830.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing water-permeable bricks have shortcomings in strength, water-permeable properties and durability, insufficient compressive and flexural strength, reduced water-permeable properties over time, poor freeze-thaw resistance and corrosion resistance, making it difficult to meet the high standards of modern urban construction and environmental engineering. .

Method used

It adopts ordinary silicate cement, light aggregate, reinforced fiber, permeable materials and active mineral blends, mix evenly through dry and wet mix, vibrating molding, combined with gas induction agent, pore-forming agent and silicone waterproofing agent, Form permeable bricks with high strength and good permeability.

Benefits of technology

The high strength, good water permeability and significant improvement in durability of permeable bricks, freeze-thaw resistance and acid-alkali environment resistance are achieved, and the service life is extended.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of water-permeable bricks, and provides a preparation method of a high-strength cement-based water-permeable brick, which comprises the following steps: selecting 30-40% by mass of ordinary Portland cement as a cementing material, selecting 20-30% by mass of lightweight aggregate, selecting 1-3% by mass of reinforced fiber, preparing 25-35% by mass of water-permeable material, and adopting an active mineral admixture to prepare the high-strength cement-based water-permeable brick. The preparation method comprises the following steps: preparing a cement-based water permeable brick with the mass ratio of 5-15%, preparing a water reducing agent with the mass ratio of 0.5-1.5%, and sequentially carrying out mixing stirring, molding treatment, maintenance treatment and surface treatment to obtain the high-strength cement-based water permeable brick. The cement-based water permeable brick disclosed by the invention realizes good balance of water permeability and strength of the cement-based water permeable brick, is relatively high in water permeability coefficient and capable of effectively draining water, and meanwhile, through reasonable material selection and proportioning, the water permeable brick is relatively high in compressive strength, excellent in breaking strength, freezing resistance and corrosion resistance and capable of meeting the requirements of various use scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of permeable brick preparation, in particular to a method for preparing high-strength cement-based permeable bricks. Background Art

[0002] Permeable bricks are a type of building material that allows rainwater and other moisture to penetrate the brick body and seep into the ground. They have a unique pore structure inside, and these pores are interconnected to form a channel for moisture migration. Permeable bricks play an important role in urban construction and environmental engineering. They can be used in a variety of places such as sidewalks, parking lots, and squares. They can not only effectively replenish groundwater resources, but also regulate surface runoff and reduce the pressure on urban drainage systems.

[0003] However, existing permeable bricks have some defects in practical applications. In terms of strength, many permeable bricks have insufficient compressive and flexural strength, and are easily damaged when subjected to vehicle rolling or heavy object impact, resulting in the brick body breaking or even crushing, which seriously limits its application in some places that need to withstand large loads; in terms of water permeability, some permeable bricks have their pore structure destroyed due to physical and chemical changes during use, causing the water permeability to be greatly reduced over time; in terms of durability, existing permeable bricks often have poor freeze-thaw resistance and corrosion resistance. In cold areas, the moisture inside the brick body will damage the brick body structure during freezing and melting, resulting in cracks in the brick body, surface peeling and other problems. In an environment corroded by acid rain or other chemicals, the performance of permeable bricks will gradually decline, the appearance and structure will be damaged, and the service life will be shortened. These defects make it difficult for existing permeable bricks to fully meet the high standards for building materials in modern urban construction and environmental engineering in actual use. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a method for preparing a high-strength cement-based permeable brick, which solves the problem that the performance of the permeable brick in the prior art is not perfect.

[0005] 1. To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing high-strength cement-based permeable bricks, comprising the following steps: S1. Ordinary Portland cement is selected as the cementitious material, accounting for 30%-40% by mass, lightweight aggregate is selected, accounting for 20%-30% by mass, reinforcing fiber is selected, accounting for 1%-3% by mass, permeable material is prepared, accounting for 25%-35% by mass, active mineral admixture is used, accounting for 5%-15% by mass, and water reducing agent is prepared, accounting for 0.5%-1.5% by mass; S2. Cement, lightweight aggregate, reinforcing fiber, permeable material, active mineral admixture and admixture are added to a mixer according to the above mass proportions, first dry-mixed to make the raw materials preliminarily mixed evenly, and then water is added to continue wet mixing to obtain a uniform mixed slurry; S3. Inject the mixed slurry into the mold. The shape and size of the mold are determined according to the design requirements of the permeable brick. Use a vibration table to vibrate the slurry in the mold to ensure that the slurry is filled densely and evenly; S4. The formed permeable brick body together with the mold is placed in a curing room for curing. After the curing period expires, the permeable brick blank is demoulded; S5. After the surface of the permeable brick blank is polished, it is impregnated with an organic silicon waterproofing agent for 1-2 hours. After impregnation, it is dried at 40-50° C. for 2-3 hours to obtain a high-strength cement-based permeable brick.

[0006] Preferably, the lightweight aggregate is ceramsite with a particle size range of 3-5 mm and a bulk density of 500-600 kg / m 3 .

[0007] Preferably, the reinforcing fiber is polypropylene fiber with a length of 6-12 mm.

[0008] Preferably, the water-permeable material is silica sand with a particle size of 0.5-2 mm.

[0009] Preferably, the active mineral admixture is fly ash, and the fineness thereof is such that the residue on a 45 μm square hole sieve does not exceed 12%.

[0010] Preferably, in S2, the dry mixing time is 3-5 minutes, the stirring speed is 100-150 rpm, the wet mixing time is 5-8 minutes, the water-cement ratio is controlled between 0.3-0.4, and the stirring speed is 150-200 rpm.

[0011] Preferably, S2 further comprises adding an air entraining agent and a pore-forming agent before dry mixing, wherein the air entraining agent is a rosin thermal polymer air entraining agent, accounting for 0.05%-0.1% by weight, and the pore-forming agent is starch, accounting for 1%-2% by weight.

[0012] Preferably, the temperature of the curing room in S4 is controlled at 20-25° C., the relative humidity is maintained at 90%-95%, the curing time is 8-12 days, and water is sprayed regularly during the curing period to keep the surface of the bricks moist.

[0013] Preferably, S3 further comprises applying a layer of release agent on the inner wall of the mold before injecting the slurry, wherein the release agent is a vegetable oil-based release agent, and the vibration frequency of the vibration table is 50-80 Hz, and the vibration time is 1-2 minutes.

[0014] Preferably, the prepared permeable bricks are subjected to quality inspection, and the inspection items include compressive strength, flexural strength, water permeability coefficient, frost resistance and corrosion resistance, and the compressive strength is required to be not less than 30MPa, the flexural strength is not less than 4MPa, and the water permeability coefficient is not less than 3×10 -2 cm / s, the mass loss after 300 freeze-thaw cycles does not exceed 5%, and there is no obvious change in appearance and the strength loss does not exceed 10% after immersion in an acid-base solution with a pH value of 3-10 for 28 days.

[0015] The present invention provides a method for preparing high-strength cement-based permeable bricks, which has the following beneficial effects: 1. The present invention achieves a good balance between the permeability and strength of cement-based permeable bricks, has a high permeability coefficient, and can effectively drain water. At the same time, through reasonable material selection and proportioning, the compressive strength of the permeable bricks reaches higher requirements, and the flexural strength is also excellent, meeting the needs of various usage scenarios.

[0016] 2. The permeable bricks prepared by the present invention have obvious advantages in durability. By introducing air entraining agents and pore-forming agents, they have excellent anti-freeze-thaw properties, and the mass loss after the freeze-thaw cycle test is small. Moreover, treatments such as impregnation with silicone waterproofing agents make them acid and alkali resistant. After being immersed in different acid and alkali environments, the changes in appearance and strength meet the requirements. They have strong ability to adapt to harsh environments and extend their service life. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] Embodiment 1: The embodiment of the present invention provides a method for preparing a high-strength cement-based permeable brick, comprising the following steps: S1. Raw material preparation Ordinary Portland cement is selected as the cementitious material, accounting for 30% by weight, and ceramsite is selected as the lightweight aggregate, with a particle size range of 3-5mm and a bulk density of 500kg / m 3, with a mass proportion of 20%. Polypropylene fiber is selected as reinforcing fiber, with a length of 6mm and a mass proportion of 1%. Silica sand is prepared as a permeable material, with a particle size of 0.5-2mm and a mass proportion of 35%. Fly ash is used as an active mineral admixture, with a fineness of 45μm square hole sieve residue not exceeding 12%, and a mass proportion of 14%. Water reducing agent is prepared, with a mass proportion of 0.5%. The initial setting time of ordinary silicate cement is not earlier than 45 minutes, and the final setting time is not later than 600 minutes. As a lightweight aggregate, ceramsite has good water absorption and air permeability, and its rough surface is conducive to bonding with cement paste; S2. Mixing and stirring The raw materials in S1 are added into a mixer according to the mass proportion, and dry-mixed for 3 minutes at a stirring speed of 100 rpm, and then water is added, and the water-cement ratio is controlled at 0.3. Wet-mixed for 5 minutes at a stirring speed of 150 rpm are continued to obtain a uniform mixed slurry, wherein 0.05% by mass of rosin thermopolymer air-entraining agent and 1% by mass of starch are added as air-entraining agent and pore-forming agent before dry mixing. During the curing process, the air-entraining agent introduces closed bubbles in the brick body, and the bubble diameter is 0.05-0.15 mm, and the bubble spacing coefficient does not exceed 0.2 mm, so as to improve the anti-freeze-thaw performance of the permeable brick. The pore-forming agent forms uniformly distributed micropores inside the brick body, and the pore size range of the micropores is 0.1-0.3 mm, and the porosity is 15%-20%, so as to ensure uniform water permeability of the permeable brick; S3. Inject the mixed slurry into the mold. Before injecting the slurry, apply a layer of vegetable oil-based release agent on the inner wall of the mold. Use a vibration table to vibrate the slurry in the mold at a frequency of 50 Hz and a vibration time of 1 minute to ensure that the slurry is filled densely and evenly. S4. The formed permeable brick body together with the mold is placed in a curing room for curing. The temperature in the curing room is controlled at 20°C and the relative humidity is maintained at 90%. The curing time is 8 days. During the curing period, water is sprayed regularly to keep the surface of the brick moist. S5. After the curing period expires, demoulding is performed to obtain a permeable brick blank, the surface of the permeable brick blank is polished, and then impregnated, the impregnation liquid is an organic silicon waterproofing agent, the impregnation time is 1 hour, and after impregnation, it is dried at 40°C for 2 hours to obtain a high-strength cement-based permeable brick. The organic silicon waterproofing agent is selected as the impregnation liquid, which has good waterproofness, air permeability and corrosion resistance, and can form a protective film on the surface of the permeable brick, which can prevent a large amount of liquid water from invading the interior of the structure without affecting the permeable gap. While ensuring the basic permeability function of the permeable brick, its impermeability can be improved to prevent excessive water from penetrating into the interior of the brick body in a short time and damaging the brick structure; The quality of the permeable bricks prepared in Example 1 was tested, and the compressive strength was 30 MPa, the flexural strength was 4 MPa, and the permeability coefficient was 3×10-2 cm / s, the mass loss after 300 freeze-thaw cycles is 5%, and there is no obvious change in appearance and the strength loss is 10% after immersion in acid-base solution with a pH value of 3-10 for 28 days.

[0019] Embodiment 2: The embodiment of the present invention provides a method for preparing a high-strength cement-based permeable brick, comprising the following steps: S1. Prepare ordinary Portland cement with a mass ratio of 35%, ceramsite particle size of 3-5mm, and a bulk density of 550kg / m 3, The mass proportion is 25%, the polypropylene fiber length is 9mm, the mass proportion is 2%, the silica sand particle size is 0.5-2mm, the mass proportion is 30%, the fly ash mass proportion is 8%, and the water reducer mass proportion is 1%; S2. After adding the raw materials in proportion, dry mix for 4 minutes, stirring speed 120 rpm, add water, water-cement ratio 0.35, wet mix for 6 minutes, stirring speed 180 rpm, 0.08% by mass of rosin thermal polymer air entraining agent 1.5% by mass and starch, added before dry mixing; S3. Inject the mold coated with vegetable oil type release agent, the vibration table vibration frequency 60Hz, vibration time 1.5 minutes; S4. The temperature of the curing room is 23℃, the relative humidity is 93%, the curing is 10 days, and water is sprayed regularly; S5. After demoulding, polishing, impregnation with silicone waterproofing agent for 1.5 hours, and drying at 45°C for 2.5 hours; The quality of the permeable bricks prepared in Example 2 was tested, and the compressive strength was 35 MPa, the flexural strength was 4.5 MPa, and the water permeability coefficient was 3.5×10 -2 cm / s, 300 freeze-thaw cycles with a mass loss of 3%, and the changes in appearance and strength after acid and alkali immersion meet the requirements.

[0020] Embodiment three: The embodiment of the present invention provides a method for preparing a high-strength cement-based permeable brick, comprising the following steps: S1. Prepare 40% of ordinary Portland cement, 3-5mm ceramsite particle size, and 600kg / m3 bulk density. 3 30% of the total, 3% of the polypropylene fiber length is 12mm, 25% of the silica sand particle size is 0.5-2mm, 5% of the fly ash, and 1.5% of the water reducing agent. S2. Put the raw materials into the mixer, dry mix for 5 minutes at 150 rpm, add water, water-cement ratio 0.4, wet mix for 8 minutes at 200 rpm, the air entraining agent is rosin thermal polymer air entraining agent 0.1%, the pore-forming agent is starch 2%, add before dry mixing, S3. The slurry is injected into the mold with a release agent and the vibration table is vibrated at 80 Hz for 2 minutes; S4. Curing room at 25℃, 95% humidity, curing for 12 days, spraying water regularly; S5. Demolding and polishing, impregnation with silicone waterproofing agent for 2 hours, and drying at 50℃ for 3 hours; The quality of the permeable bricks prepared in Example 3 was tested, and the compressive strength was 40 MPa, the flexural strength was 5 MPa, and the permeability coefficient was 4×10 -2 cm / s, 300 freeze-thaw cycles with a mass loss of 2%, and meets the requirements after acid and alkali immersion.

[0021] Comparative Example 1: The comparative example of the present invention provides a method for preparing a cement-based permeable brick, comprising the following steps: Raw material preparation: similar to Example 1, but without adding reinforcing fiber (polypropylene fiber); Mixing and stirring: dry mixing and wet mixing are carried out according to the stirring time and speed of Example 1, but without considering the addition of reinforcing fibers; Molding process: the molding process is carried out in the same manner as in Example 1; Maintenance treatment: perform maintenance treatment as in Example 1; Surface treatment: Surface treatment is performed in the same manner as in Example 1; The quality of the permeable bricks prepared in the above comparative example 1 was tested, and the compressive strength was 25MPa, the flexural strength was 3MPa, and the permeability coefficient was 3×10 -2 cm / s, 300 freeze-thaw cycles with a mass loss of 6%, and after immersion in an acid-base solution with a pH value of 3-10 for 28 days, the appearance showed slight peeling and the strength loss was 10%.

[0022] Comparative Example 2: The comparative example of the present invention provides a method for preparing a cement-based permeable brick, comprising the following steps: Raw material preparation: similar to Example 2, but without adding air entraining agent (rosin thermal polymer air entraining agent) and pore-forming agent (starch); Mixing and stirring: dry mixing and wet mixing are performed according to the stirring parameters of Example 2, but no air entraining agent and pore forming agent are added; Molding process: the molding process is carried out in the same manner as in Example 2; Maintenance treatment: perform maintenance treatment as in Example 2; Surface treatment: Surface treatment is performed in the same manner as in Example 2; The quality of the permeable bricks prepared in the above ratio 2 was tested, and the compressive strength was 30MPa, the flexural strength was 4MPa, and the permeability coefficient was 2.5×10 -2 cm / s, 300 freeze-thaw cycles with a mass loss of 8%, and after immersion in an acid-base solution with a pH value of 3-10 for 28 days, there are a few cracks on the surface and the strength loss is 15%.

[0023] In summary, the cement-based permeable bricks prepared by the present invention have high brick body strength while maintaining good water permeability, and have strong anti-freeze and corrosion resistance. They can be used stably for a long time in different environments and have a long service life.

[0024] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing high-strength cement-based permeable bricks, characterized in that: The following steps are involved: S1. Ordinary Portland cement is selected as the cementitious material, accounting for 30%-40% by mass, lightweight aggregate is selected, accounting for 20%-30% by mass, reinforcing fiber is selected, accounting for 1%-3% by mass, permeable material is prepared, accounting for 25%-35% by mass, active mineral admixture is used, accounting for 5%-15% by mass, and water reducing agent is prepared, accounting for 0.5%-1.5% by mass; S2. Cement, lightweight aggregate, reinforcing fiber, permeable material, active mineral admixture and admixture are added to a mixer according to the above mass proportions, first dry-mixed to make the raw materials preliminarily mixed evenly, and then water is added to continue wet mixing to obtain a uniform mixed slurry; S3. Inject the mixed slurry into the mold. The shape and size of the mold are determined according to the design requirements of the permeable brick. Use a vibration table to vibrate the slurry in the mold to ensure that the slurry is filled densely and evenly; S4. The formed permeable brick body together with the mold is placed in a curing room for curing. After the curing period expires, the permeable brick blank is demoulded; S5. After the surface of the permeable brick blank is polished, it is impregnated with an organic silicon waterproofing agent for 1-2 hours. After impregnation, it is dried at 40-50° C. for 2-3 hours to obtain a high-strength cement-based permeable brick.

2. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: The lightweight aggregate is ceramsite with a particle size range of 3-5 mm and a bulk density of 500-600 kg / m3.

3. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: The reinforcing fibers are polypropylene fibers with a length of 6-12 mm.

4. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: The water-permeable material is silica sand with a particle size of 0.5-2 mm.

5. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: The active mineral admixture is fly ash, and the fineness thereof is such that the residue on a 45 μm square hole sieve does not exceed 12%.

6. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: In S2, the dry mixing time is 3-5 minutes, the stirring speed is 100-150 rpm, the wet mixing time is 5-8 minutes, the water-cement ratio is controlled between 0.3-0.4, and the stirring speed is 150-200 rpm.

7. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: The S2 also includes adding an air entraining agent and a pore-forming agent before dry mixing, wherein the air entraining agent is a rosin thermal polymer air entraining agent, accounting for 0.05%-0.1% by weight, and the pore-forming agent is starch, accounting for 1%-2% by weight.

8. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: The temperature of the curing room in S4 is controlled at 20-25°C, the relative humidity is maintained at 90%-95%, the curing time is 8-12 days, and water is sprayed regularly during the curing period to keep the surface of the bricks moist.

9. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: The S3 also includes applying a layer of release agent on the inner wall of the mold before injecting the slurry, wherein the release agent is a vegetable oil-based release agent, and the vibration frequency of the vibration table is 50-80 Hz, and the vibration time is 1-2 minutes.

10. The method for preparing a high-strength cement-based permeable brick according to claim 1, characterized in that: It also includes quality inspection of the prepared permeable bricks. The inspection items include compressive strength, flexural strength, water permeability, frost resistance and corrosion resistance. The compressive strength is required to be no less than 30MPa, the flexural strength is no less than 4MPa, the water permeability is no less than 3×10-2cm / s, the mass loss after 300 freeze-thaw cycles is no more than 5%, and there is no obvious change in appearance after immersion in an acid-base solution with a pH value of 3-10 for 28 days, and the strength loss does not exceed 10%.